2014
DOI: 10.1080/09540121.2014.921278
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in HIV disclosure, stigma, and perceptions of health

Abstract: HIV disclosure is a gateway to HIV prevention - particularly among couples living in regions severely affected by the HIV epidemic. This cross-sectional study utilizes data collected from 862 people living with HIV across three countries (Ethiopia, Mozambique, and Uganda) in 2011 to determine the role of partner disclosure on self-reported health perceptions and changes in sexual risk behavior. The study's secondary aims are to understand whether or not internalized stigma mediates this relationship and if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…It is, therefore, possible that a high level of spirituality may enhance PLWHs' confidence in the future, as this could foster a comforting sense of life meaning and inner peace, and promote a successful life with HIV (Porter, Brennan-Ing, Burr, Dugan, & Karpiak, 2017;Rueda et al, 2014). The path model suggested that women were more likely than men to report increased self-stigma, which was consistent with findings in both higher- (Logie et al, 2011;Loutfy et al, 2012) and lower-income countries (Geary et al, 2014). Possible explanations may be general social differences between men and women, gender-related social status differences due to HIV, and inherent social expectations concerning women in that society (e.g., pregnancy), which may lead to social rejection (Darlington & Hutson, 2017;Logie, James, Tharao, & Loutfy, 2013;Loutfy et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…It is, therefore, possible that a high level of spirituality may enhance PLWHs' confidence in the future, as this could foster a comforting sense of life meaning and inner peace, and promote a successful life with HIV (Porter, Brennan-Ing, Burr, Dugan, & Karpiak, 2017;Rueda et al, 2014). The path model suggested that women were more likely than men to report increased self-stigma, which was consistent with findings in both higher- (Logie et al, 2011;Loutfy et al, 2012) and lower-income countries (Geary et al, 2014). Possible explanations may be general social differences between men and women, gender-related social status differences due to HIV, and inherent social expectations concerning women in that society (e.g., pregnancy), which may lead to social rejection (Darlington & Hutson, 2017;Logie, James, Tharao, & Loutfy, 2013;Loutfy et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with previous reports in HIV-positive individuals (Obermeyer et al, 2011; Vu et al, 2012), but is concerning because of missed opportunities to offer HIV testing and referral to either treatment or prevention. Our findings of strong correlates support existing literature regarding common correlates of non-disclosure to partners, including being female, not being in a steady partnership, and not knowing the partner’s status (Abdool Karim et al, 2015; Daftary & Padayatchi, 2012; DiCarlo et al, 2014; Geary et al, 2014; Longinetti et al, 2014; Przybyla et al, 2013; Reda, Biadgilign, Deribe, & Deribew, 2013). …”
Section: Discussionsupporting
confidence: 86%
“…Concealment of HIV-positivity may expose HIV-negative partners to infection, increase reinfection among HIV-positive partners, and create missed opportunities for HIV care (King et al, 2008; Vu et al, 2012). Studies in both rural and urban settings across sub-Saharan Africa have shown disclosure of HIV-positivity to be associated with positive outcomes including increased social support (Maman et al, 2003; Ogoina et al, 2015), reduced internalized stigma (Geary et al, 2014), improved mental health (King et al, 2008), and safer sexual behaviors (Rujumba et al, 2012). Other research in the region associates disclosure to sexual partners with increased understanding and support (Medley, Garcia-Moreno, McGill, & Maman, 2004; Obermeyer et al, 2011), trust (Atuyambe et al, 2014; King et al, 2008), and HIV care uptake (Deribe, Woldemichael, Wondafrash, Haile, & Amberbir, 2008; King et al, 2008).…”
Section: Introductionmentioning
confidence: 99%